Isothermal and Cyclic Oxidation of MoAlB in Air from 1100°C to 1400°C. Issue 13 (1st January 2017) - Kota, Sankalp; Zapata-Solvas, Eugenio; Chen, Yexiao; Radovic, Miladin; Lee, William E.; Barsoum, Michel W.
Abstract : Like many FeCrAl-based alloys, and some MAX phases, the atomically laminated boride, MoAlB, forms slow-growing, adherent Al2 O3 scales when heated in air to 1350°C. Herein the oxidation of MoAlB ceramics in air was studied in the 1100–1400°C temperature range for up to 200 h. At 1400°C, the oxide scale was heavily cracked and spalled. At 1100°C, and up to 20 h, mass loss was recorded. At 1300°C and 1350°C, subparabolic, approximately cubic kinetics were observed, as a result of growth and coarsening of the Al2 O3 grains in the oxide scale. At 1200°C, the weight gain kinetics were nearly linear, while the oxide thickening kinetics were approximately cubic likely due to cubic growth of Al2 O3 and concurrent volatility of constituents in the oxide scale. The cyclic oxidation resistance was also good for up to 125, 1-hour, cycles at 1200°C. Analysis of grain coarsening and scale thickening kinetics suggest that oxygen grain boundary diffusivity is the rate controlling mechanism for the growth of Al2 O3 scales at 1300°C and 1350°C. Dimensional changes at samples' corners after long oxidation at T > 1200°C may limit the maximum operational temperature of MoAlB.